Reviews. (1st July 2014) - Crook, Tim; Raw, Laurence
Theater of the Mind: Imagination, Aesthetics, and American Radio Drama, Neil Verma (2012) Chicago & London: The University of Chicago Press, 296 pp., ISBN: p/bk 978-0226853512, £21.50, h/bk 978-0226853505, £63.00Science Fiction, Film, Television, and Adaptation: Across the Screens, J. P. Telotte and Gerald Duchovnay (eds) (2012) London and New York: Routledge, 212 pp., ISBN 9780415887199, h/bk, Price £88.99